Elämää sinnittelevässä pikkukaupungissa varkautelaisten arki ja hyvinvointi - Hänninen, Vilma; Kouvo, Antti; Kuusela, Pekka (Tampere University Press, 2020)
The ten articles in this edited volume examine the city of Varkaus as a small city struggling with structural change using historical documents as well as survey and interview data. The city of Varkaus, which has a long industrial history, has lost a large part of its industrial jobs in the first decades of this millennium and its population has fallen sharply in recent years. However, a survey of the adult population shows that the inhabitants of Varkaus are typically satisfied with their work, with their social relationships and their lives in general. Varkaus is seen as a safe and good living environment. A central element of well-being is couple relationship, as well as other social relationships. The lack of well-being often stems from unemployment, low income and feelings of not belonging to the place of residence. Young adults value their place of residence as well as their family relationships, but there are tensions in their life regarding work and income. The tranquility and proximity to nature of Varkaus are appreciated, but there are also many who long for more urban heartbeat in their hometown.